2020
DOI: 10.1163/2031356x-03301006
|View full text |Cite
|
Sign up to set email alerts
|

Structure et Régénération des Peuplements Naturels de Balanites Aegyptiaca (L.) Del. Et Ziziphus Mauritiana Lam. Suivant un Gradient Écologique dans la Région de Maradi au Niger

Abstract: Les espèces ligneuses jouent un rôle important dans la vie des populations locales. Parmi les espèces couramment utilisées au Niger figurent Balanites aegyptiaca et Ziziphus mauritiana. Ces deux espèces sont exploitées comme sources alimentaires et pour divers produits médicinaux, avec comme conséquence une réduction de leurs peuplements. La présente étude vise à analyser la structure des peuplements et les modes de régénération des deux espèces dans deux secteurs agro-écologiques contrastées de la région de M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Researchers at ORSTOM (now IRD) have always found that farmers intensify mainly on the fields close to their homes and that agriculture becomes more extensive when moving away from the village. Dan Saga had an average density of 74 trees/hectare in 2009, but Rabiou et al (2020) report an average density of 153 trees/hectare in this village just 10 years later. The phenomenon of protection and management of natural regeneration is older in the villages of the Zinder region, where customary legislation in Damagaram prohibited the felling of a Faidherbia albida tree at the risk of decapitation.…”
Section: Characterization Of Woody Vegetation Structurementioning
confidence: 85%
See 1 more Smart Citation
“…Researchers at ORSTOM (now IRD) have always found that farmers intensify mainly on the fields close to their homes and that agriculture becomes more extensive when moving away from the village. Dan Saga had an average density of 74 trees/hectare in 2009, but Rabiou et al (2020) report an average density of 153 trees/hectare in this village just 10 years later. The phenomenon of protection and management of natural regeneration is older in the villages of the Zinder region, where customary legislation in Damagaram prohibited the felling of a Faidherbia albida tree at the risk of decapitation.…”
Section: Characterization Of Woody Vegetation Structurementioning
confidence: 85%
“…Currently, villagers are reintroducing species that disappeared in the 1970s and 1980s (Zarafi, 2002;Larwanou and Saadou, 2005). On RNA sites, tree density can be as high as 153 trees per hectare in Dan Saga, in contrast to non-RNA sites where the density does not exceed 40 trees/ha (Baggnian et al, 2019;Rabiou et al, 2020).…”
Section: Biodiversitymentioning
confidence: 99%